What value do stock analysts bring with their recommendations? : evidence from the US and the brazilian markets - Medeiros, Raphael Rique Uchôa de (2020)
This paper investigates the impact of changes in analysts’ recommendations on stock market prices over the 2006 – 2018 period, for two distinct markets. I find that, for the US market, both upgrades and downgrades generate abnormal returns on the day of the recommendation revision, with downgrades producing larger absolute returns. Surprisingly, no-change on the recommendation also generate abnormal returns. Considering the Brazilian market, I find evidence which confirms the existence of abnormal returns, although not as significant as in the US. Extending the event window to 5 days, I find that upgrades and downgrades from the US market are also significant for all models, generating even more returns at this extended period. On the other hand, in the he Brazilian market I find no significant results for most portfolios, with the exception of the ones with the smallest changes in recommendations. When comparing by market value, smaller firms generate larger returns than larger firms on the NYSE market for all portfolios. Meanwhile for the BOVESPA market, only for the largest changes in recommendations, the smaller market value firms produce larger returns. Overall, the analysts’ recommendations for the US market are more impactful to stock prices than the recommendations for the Brazilian market.